Dual output high frequency boost converter. (2022) - Jomi, Stefi; Paul, Elizabeth; Joseph, Ashna; Eldhose, K.A.
Abstract: High step up gain boost converters with lower component counts and lower voltage stress are widely required for the modern power electronic system. A high gain boost converter with dual power output and lower component stress is presented. One of the switches attains ZVS (zero voltage switching) and the diodes attain ZCS (zero current switching). Hence the switching losses are reduced. The inductor operates on CCM (continuous conduction mode) hence smoothes the input current and can be used in renewable energy applications. This converter has improved gain, low voltage stress and lower component counts when compared with other high gain topologies. Moreover the dual power output makes the application wider. All the elements are designed to operate in high frequency. The study of performance of the converter is carried out through MATLAB/ SIMULINK R2017b for 350 W/580 kHz.